HOUT-24. DURAMATRIX-ONLAY® PLUS IN CRANIAL SURGERY IS ASSOCIATED WITH AN ACCEPTABLE COMPLICATION PROFILE: A CASE SERIES. (5th November 2018) - Udawatta, Methma; Lagman, Carlito; Sheppard, John; Nguyen, Thien; Prashant, Giyarpuram; Yang, Isaac
Abstract: BACKGROUND: DuraMatrix Onlay® Plus (Stryker, Kalamazoo, Michigan) is a collagen dura membrane derived from purified bovine Achilles tendon. The matrix provides a scaffold for collagen synthesis and is intended to be used as an onlay without the need for dural sutures. OBJECTIVE: To describe our experience with 33 consecutive patients who underwent a duraplasty procedure using the novel DuraMatrix Onlay® Plus collagen dura membrane. METHODS: This is a retrospective case series of consecutive patients who underwent a duraplasty procedure at a single academic hospital in Los Angeles, California between May 2016 and March 2017. The primary outcome is the rate of cerebrospinal fluid (CSF) leak. Secondary outcomes include the rates of dural substitute complication, infection, and removal. RESULTS: Thirty-three patients underwent a duraplasty procedure using the DuraMatrix Onlay® Plus material. The average age of the patients was 41 ± 21 years (range 2–75 years). There were 18 females and 15 males. The majority of procedures were elective and for resection of a lesion (n = 19, 58%), with the average size of material used measured at 18 ± 14 cm2. There were no secondary CSF leaks at an average follow-up of 3 months. The rates of dural substitute complication, infection, and removal were 6%, 6%, and 3%, respectively. In one patient, the dural substitute was removed for concern of infection. CONCLUSION: DuraMatrix-Onlay® Plus is associated with an acceptable complication profile, including a low rate of CSF leak.